2015
DOI: 10.1002/stem.1865
|View full text |Cite
|
Sign up to set email alerts
|

Functional Regulation of Adipose-Derived Stem Cells by PDGF-D

Abstract: Platelet-derived growth factor-D (PDGF-D) was recently identified, and acts as potent mitogen for mesenchymal cells. PDGF-D also induces cellular transformation and promotes tumor growth. However, the functional role of PDGF-D in adipose-derived stem cells (ASCs) has not been identified. Therefore, we primarily investigated the autocrine and paracrine roles of PDGF-D in this study. Furthermore, we identified the signaling pathways and the molecular mechanisms involved in PDGF-D-induced stimulation of ASCs. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…Moreover, hypoxia increases ASCs proliferation through HIF-1α activation [38], and VEGF stimulates ASCs growth VEGF [39]. Both Hye and Gehmert found that PDGF pretreatment of ASCs before transplantation increased neovascularization [4041]. We found that HIF-1α and VEGF protein and mRNA levels were increased by treatment with G-Rg1, PRF.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, hypoxia increases ASCs proliferation through HIF-1α activation [38], and VEGF stimulates ASCs growth VEGF [39]. Both Hye and Gehmert found that PDGF pretreatment of ASCs before transplantation increased neovascularization [4041]. We found that HIF-1α and VEGF protein and mRNA levels were increased by treatment with G-Rg1, PRF.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have confirmed the involvement of the CD140b receptor in the generation of mitochondrial ROS (Hye Kim, Gyu Park, Kim, Song, & Sung, ), the CD184 receptor in the chemotactic effects of SDF1α on human ASCs subjected to hypoxia (Thangarajah et al, ) and the CD271 receptor in the immunomodulatory properties of mesenchymal stem cells (Kuçi et al, ). Thus, we subsequently quantified the percentage of ASCs expressing these receptors.…”
Section: Resultsmentioning
confidence: 70%
“…According to the proposed type I binding mode for CP‐673451, different incubation times had no significant effect on PDGFRβ kinase activity (IC 50 values: 0 min=7 n m , 60 min=8 n m , 120 min=11 n m ). Thus, in line with earlier reports, these data provide further evidence for CP‐673451 being a type I inhibitor . In contrast, compound 5 blocking PDGFRβ activity was determined to be considerably time dependent (IC 50 values: 0 min=143 n m , 10 min=60 n m , 120 min=20 n m ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in line with earlier reports,t hese data provide furthere vidence for CP-673451 being at ype Ii nhibitor. [55] In contrast, compound 5 blocking PDGFRb activity was determined to be considerably time dependent (IC 50 values: 0min = 143 nm,1 0min = 60 nm,1 20 min = 20 nm). In fact, over ap eriod of 120 min, the IC 50 values of 5 weres hifted by af actor of seven toward higherP DGFRb affinity.T hese re- Figure 6.…”
Section: Biological Evaluationmentioning
confidence: 95%